The Cross-Talks Among Bone Morphogenetic Protein (BMP) Signaling and Other Prominent Pathways Involved in Neural Differentiation - Manzari-Tavakoli, Asma; Babajani, Amirhesam; Farjoo, Mohammad Hadi; Hajinasrollah, Mostafa; Bahrami, Soheyl; Niknejad, Hassan (Frontiers in Molecular Neuroscience, 2022)
The bone morphogenetic proteins (BMPs) are a group of potent morphogens which are critical for the patterning, development, and function of the central nervous system. The appropriate function of the BMP pathway depends on its interaction with other signaling pathways involved in neural differentiation, leading to synergistic or antagonistic effects and ultimately favorable biological outcomes. These opposite or cooperative effects are observed when BMP interacts with fibroblast growth factor (FGF), cytokines, Notch, Sonic Hedgehog (Shh), and Wnt pathways to regulate the impact of BMP-induced signaling in neural differentiation. Herein, we review the cross-talk between BMP signaling and the prominent signaling pathways involved in neural differentiation, emphasizing the underlying basic molecular mechanisms regarding the process of neural differentiation. Knowing these cross-talks can help us to develop new approaches in regenerative medicine and stem cell based therapy. Recently, cell therapy has received significant attention as a promising treatment for traumatic or neurodegenerative diseases. Therefore, it is important to know the signaling pathways involved in stem cell differentiation toward neural cells. Our better insight into the cross-talk of signaling pathways during neural development would improve neural differentiation within in vitro tissue engineering approaches and pre-clinical practices and develop futuristic therapeutic strategies for patients with neurological disease.